PENGGUNAAN MODUL BAHASA INGGRIS UNTUK MENGAJAR MAHASISWA PGSD - Veronika Unun Pratiwi; Nurnaningsih Nurnaningsih; Mas Sulis Setiyono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
English as an International language, as a language of communication is a foreign language that is considered to be used in the curriculum of learning in Indonesia. English is considered very important for the purpose of developing science, technology, and culture and is used to build international cooperation (Depdikbud, 1981). English learning includes 4 skills namely; reading, writing, speaking,and writing. The four skills are related to each other and can not be separated. The main objective of this research is to provide English subjects for PGSD students, especially to provide basic education about English learning activities in Elementary School. Non-English study programs within the Veteran Bangun Nusantara Sukoharjo University also teach English courses as general courses which include the material design and how to present it, from the things mentioned above, it will be used as the background to reveal the problems which will bediscussed in this study. The reason why the English course is given to non-English students in this case is elementary school students (PGSD), especially at Veteran Bangun Nusantara Sukoharjo University, is to pursue the development of the world in science and technology. The target of the output to be achieved is enrichment of English lecture materials for PGSD students in addition to the module making as a guideline for English lectures and scientific publications for this PDP research.Based on the research focus, this type of research includes qualitative descriptive research. The subjects of this study are non-English students Univet Bantara Sukoharjo, especially PGSD students.This subject is considered a beginner category in English language learning. Veteran Bangun Nusantara Sukoharjo University as a place to conduct research.Keywords: English, PGSD students, modules